Digital Literacy as a Catalyst for Regional Innovation: A Case Study of Regional Governance and Smart Community Development in Jayapura Regency - Belfin Aldriano Bonai; Mohammad Rezza Fahlevvi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Digital transformation in the Society 5.0 era requires communities to utilize technology optimally. Jayapura Regency faces serious digital literacy problems, as reflected in the 2025 Indonesian Digital Society Index (IMDI) score of 39.60, which is below the national average of 44.53, with a decline in the digital literacy pillar of 17.97 points. The availability of infrastructure does not automatically improve community capacity, thereby hindering the achievement of SDG 9 and readiness toward Smart Society 5.0. The purpose of this study is to analyze digital literacy through the five pillars of the UNDP Digital Transformation Framework, identify local government governance policies, and formulate recommendations for strengthening digital literacy as a catalyst for innovation. This research uses a qualitative approach with a descriptive-exploratory case study method. Data were collected through in-depth interviews with informants, field observations, and documentation. Informants were selected using purposive sampling, and the data were analyzed through technique triangulation. The results show that Jayapura Regency is at a developing stage, but no pillar has yet reached optimal maturity. The study recommends establishing district-level digital literacy centers, mapping blank spot areas, developing a 5–10 year Digital Transformation Roadmap, and strengthening a digital ecosystem that is adaptive toward Smart Society 5.0.